Time Poverty and Parenthood: Who Has Time for College?. (May 2021) - Conway, Katherine M.; Wladis, Claire; Hachey, Alyse C.
Student parents are among the least likely student groups to complete college. Regression models were run using 2003–2019 American Time Use Survey data to explore time poverty among college students. Results indicate that students with children under 13 years had significantly less discretionary time and free time, spent significantly less time on their education, enrolled part-time at significantly higher rates, and spent significantly more time studying while simultaneously caring for children, compared with students without children under 13 years. The strength of these relationships was strongest when children were younger. Parents with children under 6 years, and mothers of children of all age-groups, had significantly higher time poverty than other groups, yet spent significantly more time on education after controlling for discretionary time, at the cost of significantly less free time for themselves. Results suggest that improving college outcomes for student parents may require consideration of time poverty.